Reusability of macroalgae (Euchema Spinosum) as biosorbent for dye removal - Nur Najiha, Ahmad Johari (2018)
In this research, biosorption and desorption of Methylene Blue (MB) dye from red macroalga, Euchema Spinosum (E. Spinosum) were observed. Biosorption-desorption experiment were conducted to determine the most effective eluent for dye desorption and investigate the reusability of macroalgae as biosorbent. Among of the six eluents used, the most effective eluent to be found was nitric acid (HNO3). For reusability of the macroalgae, the four successive cycles of biosorption-desorption tests were obtained that show dye sorption efficiency decreased from 94.51% to 48.45% as well as desorption efficiency which is decreased from 51% to 23.4%. As for the effect of the concentration, the result indicated that 1.0M HNO3 obtained higher desorption efficiency using different pH level (pH1-pH5) in which it decreased from 31.98% to 25.71%, rather than desorption efficiency of 0.5M HNO3 which is decreased from 27.42% to 25.43%. However, high concentration may lead to the destruction of biosorbent structure, to tackle this problem further studies need to implement by using any other eluent with low concentration in order to avoid possible damage on biosorbent structure. Hence, distilled water is used and potential to be used as low cost eluent as the result obtained show that desorption efficiency was decreased from 26.26% to 21.94% from pH 1 to pH 5. In conclusion, the results of this study suggest that studied of macroalgae can favorably use as environmentally friendly and efficient sorbent for dye removal.